Efektivitas Sediaan Pelembab Bahan Alam dalam Mengatasi Kulit Kering - Dhea Quraeny Herawan; Gita Silpiani Kurnia; Indriani Sukmawati; Nia Yuniarsih (Jurnal Health Sains, 2022)
Dry skin is defined to describe the loss or decrease in the moisture content of the Stratum Corneum (SC). Skin looks healthy when the outer layer contains 10% water. Research has been carried out on the effectiveness of natural ingredients moisturizing preparations in overcoming dry skin. The purpose of this study was to determine the optimal effectiveness of natural ingredients to increase skin moisture in overcoming dry skin. Generally, skin moisturizing cosmetics consist of moisturizing ingredients that can form artificial skin surface fat to flex the dry and rough skin layer, and reduce evaporation of water from the skin. So, there are several natural ingredients that will help moisturize the skin and deal with dry skin.